(untitled) (Annual of the Faculty of Philosophy in Skopje, 2022)
In the last few decades we have witnessed a proliferation of works in the field widely defined as “studies of the relationship between man and animals”, “studies of animals”, or “anthrozoology”, and even “studies of animal ethics”. Among the avant-garde in this field there is a confrontation with this naturalized discourse. Over time, this has led to a growing need to reconsider, analyse and upgrade the validity of the argument of different ethical views and their theories that serve to determine and evaluate our behaviour towards animals as morally acceptable or not. Hence, what the author is primarily concerned with, is critical reflection on a wide range of theories that seek to explain relevant positions on our relationship to animals and wildlife on Earth. Taking on this new responsibility in relation to our treatment of animals modifies not only our way of more direct treatment of animals, but also the way we should be constituted as entities in the world. It is an assumption that we share the world with other beings and that this implies a moral obligation that goes beyond the category of belonging to the same species. A new culture of human coexistence with other non-human beings needs to be inaugurated, in line with modern living conditions on this planet.